推動高等教育校務經營全面品質管理之研究－以國立清華大學為實證 - 簡禎富; 侯建良; 吳建瑋; 林國義; 胡益芬; 朱珮君; Chen-Fu Chien Jiang-Liang Hou Chien-Wei Wu Kuo-Yi Lin Yi-Fen Hu Pei-Chun Chu (國立交通大學, 2017)
在全球知識經濟競爭的環境下，台灣高等教育除了面臨少子化、國際化及全球化的困境與衝擊外，更有吸引國際一流人才及經費自籌的壓力，造成高等教育經營管理的嚴峻挑戰。在有限的高等教育資源中，如何藉由管理方法與技術，協助校務經營與持續發展以提升競爭力，為高等教育持續提升的關鍵。本研究目的為建立高等教育全面品質管理系統性架構，回顧歐美各國高等教育實施全面品質管理的歷程及台灣高等教育之經營現況，了解高等教育面對的問題，提出以紫式決策分析架構為基礎的高等教育提升全面品質的推動架構，包含瞭解問題、界定利基、架構影響、客觀敘述、主觀衡量與決策執行，並以國立清華大學通過國家品質獎為實例，說明推動歷程與成效。研究結果可提供政府、產學研各界及大學，在擬定高教政策、產學合作及推動校務全面品質管理時的參考。

As the increased acceleration and intensity of global knowledge economy competition, Taiwanese higher education faces the challenge of low birth rate, resources shortage and exploitation of experts' attraction. Therefore, to improve the competiveness of higher education has become an urgent need and important issue for Taiwan. This study aims to propose a higher educational total quality management framework to enhance the quality to improve the competitiveness of Taiwanese higher education. The proposed framework includes six steps: understand problem, identify niche, the influence of structure, objective description outcomes, subjective assessments, and decision and execution. To validate the proposed framework, an empirical study has conducted by National Tsinghua University through obtained the National Quality Award examples of how to promote the process and performance. The results provide decision support of higher education for government policy and university strategy. The proposed UNSION model was constructed as to propose a blueprint for implement the TQM of higher educations for sustainable development.
Investigation of Total Quality Management in Higher Education Institutional Research: An Empirical Study of National Tsing Hua University
Keywords: 簡禎富; 侯建良; 吳建瑋; 林國義; 胡益芬; 朱珮君; Institutional Research; Higher Educational Management; Total Quality Management (TQM); National Quality Award (NQA); Sustainable development; Decision Quality